Yanna Tzourmana, Βρετανοί ριζοσπάστες μεταρρυθμιστές: Φιλικές εταιρείες και κομιτάτα στο Λονδίνο (1790-1823) [British radical reformers: friendly societies and committees in London, 1790-1823] - Sotiropoulos, Michail (Historein, 2018)
Yanna Tzourmana. Βρετανοί ριζοσπάστες μεταρρυθμιστές: Φιλικές εταιρείες και κομιτάτα στο Λονδίνο (1790-1823) [British radical reformers: friendly societies and committees in London, 1790-1823]. Athens: Benaki Museum, 2015. 360 pp.